Determination of Friction Angles Between Soil and Steel - FRP Piles - Aksoy, H. Suha; Gör, Mesut; İnal, Esen (Fırat University, 2018)
Forces of friction between structure and soil are taken into account in the design of geotechnical engineering constructions such as piles, retaining walls, sheet piles and diaphragm walls. Although many studies were carried out about the soil-structure interaction in recent years.  However, in pile design, frictional forces are still calculated by using the empirical formulas proposed in the first half of the 20th century. Throughout history, wood was often used as friction piles. Steel piles are used extensively in practice. Nowadays, in harsh environmental conditions fiber-reinforced polymer (FRP) piles come into use in numerous cases.   As is known, the effect of pile point tip resistance on the bearing capacity is ignored particularly in loose sands and the bearing capacity is fully taken equal to the skin friction. Hence, it is understood that correct determination of skin friction angle is very important in engineering calculations. In this study, various ratios of low plasticity clays (CL) were added to the sandy soil and compacted to standard Proctor density. Thus, soils with various internal friction angles were obtained. By performing interface shear tests (IST), skin friction angles of these soils with steel (st37) and FRP were determined. Based on the data obtained from the test results, a chart was proposed, which engineers can use in pile design. By means of this chart, the skin friction angles of the soils, of which only the internal friction angles are known, with steel and FRP materials can be determined easily.
Keywords: Engineering; Mühendislik